Use of electron irradiation versus formaldehyde fumigation as hatching egg disinfectants – efficacy and impact on hatchability and broiler performance - Pees, Michael; Motola, Gerzon; Hafez, Mohamed Hafez; Bachmeier, Josef; Brüggemann-Schwarze, Sarah; Tebrün, Wiebke (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2020)
Objective The use of low-energy electron irradiation for hatching egg disinfection was compared to formaldehyde fumigation.Material and methods To assess the efficacy, eggshells were examined for bacteria before and after disinfection. During incubation, hatching and fattening of 1400 Ross 308 broilers per group candling data, hatching rate, mortality rate and body mass development were recorded to evaluate the impact on health and performance. Additionally, data from the slaughter house and histological evaluation of organ samples were included in the health screening.Results Regarding the efficacy, irradiation and formaldehyde significantly reduced the number of bacteria compared to non-disinfected eggs. However, no significant difference was recorded between both treatments. The irradiated group performed better than the reference group concerning the number of infertile eggs, early and late dead embryos and fertile eggs. The performance during fattening was nearly identical in both groups, while mortality differed slightly between the irradiated group and the group treated with formaldehyde. Upon slaughter, there were minor variations concerning the distribution of findings between the groups, but the number of anomalies was not higher than reference values suggest.Conclusion In both groups no health problems were observed during rearing and the fattening performance met the targets of the manufacturer Aviagen for the used broiler line Ross 308.Clinical relevance Lower-energy electron irradiation proves to be an efficient and well-tolerated hatching egg disinfection procedure. Further field trials are necessary to establish low-energy electron irradiation as an alternative to formaldehyde fumigation.
Keywords: Poultry; fattening; hatching egg hygiene; decontamination